2008
DOI: 10.1103/physrevb.78.134408
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of the charge-density-wave compoundCeTe2

Abstract: The temperature dependence of the optical conductivity of CeTe 2 was obtained for the E ʈ ab plane and E ʈ c axis at photon energies ranging from terahertz to visible light. Two gap states are found in the optical conductivity spectra. The magnitudes of the gaps are estimated to be 0.448 and 0.109 eV in the E ʈ ab plane. The former is due to perfect nesting, while the latter is due to imperfect nesting. The magnitude of the gap due to perfect nesting on the c axis is evaluated to be 0.854 eV. The Drude respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(22 reference statements)
2
2
0
Order By: Relevance
“…The reduction of the CDW gap near the  point can be explained by the imperfect nesting near this momentum region, which has also been observed in other RETe3 CDW materials [41,42]. The large CDW gap observed in CeSbTe is comparable to CeTe2 (with a half gap ~0.2 eV) [47,48] and CeTe3…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The reduction of the CDW gap near the  point can be explained by the imperfect nesting near this momentum region, which has also been observed in other RETe3 CDW materials [41,42]. The large CDW gap observed in CeSbTe is comparable to CeTe2 (with a half gap ~0.2 eV) [47,48] and CeTe3…”
Section: Resultssupporting
confidence: 52%
“…The reduction of the CDW gap near the point can be explained by the imperfect nesting near this momentum region, which has also been observed in other RETe 3 CDW materials [41,42]. The large CDW gap observed in CeSbTe is comparable to CeTe 2 (with a half gap~0.2 eV) [47,48] and CeTe 3 (with a half gap~0.2 eV) [40,49], indicating that their CDW orders share much in common. The large CDW gap also provides a natural explanation for the robustness of the CDW order even at high temperatures.…”
Section: Resultsmentioning
confidence: 52%
“…2(c) and 2(d). The CDW gaps are found to open only partially in some part of the FS, which is consistent with the semimetallic nature of RTe 2 [17,27,28]. The overall similarity of the FS/CE maps of CeTe 2 and PrTe 2 , as well as those of LaTe 2 [15], implies that the contribution of the R 4f (R = Ce, Pr) electrons to the states at E F is minor.…”
Section: Resultssupporting
confidence: 64%
“…Second, the opening of the CDW gaps occurs only partially in some part of the FS, which is consistent with the semimetallic nature of CeTe 2 . 2,18,19 Recently, Johannes and Mazin 20 showed that the FS nesting does not necessarily produce a peak in the susceptibility χ (q) that leads to the CDW instability. given wave vector q ("nesting") or from the parallel bands spanned by a q vector ("volume effects").…”
Section: Experimental and Calculational Detailsmentioning
confidence: 99%